2017 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations Summary. Issue 23 (5th December 2017) - Olasveengen, Theresa M.; de Caen, Allan R.; Mancini, Mary E.; Maconochie, Ian K.; Aickin, Richard; Atkins, Dianne L.; Berg, Robert A.; Bingham, Robert M.; Brooks, Steven C.; Castrén, Maaret; Chung, Sung Phil; Considine, Julie; et al.
Abstract : The International Liaison Committee on Resuscitation has initiated a near-continuous review of cardiopulmonary resuscitation science that replaces the previous 5-year cyclic batch-and-queue approach process. This is the first of an annual series of International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations summary articles that will include the cardiopulmonary resuscitation science reviewed by the International Liaison Committee on Resuscitation in the previous year. The review this year includes 5 basic life support and 1 pediatric Consensuses on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. Each of these includes a summary of the science and its quality based on Grading of Recommendations, Assessment, Development, and Evaluation criteria and treatment recommendations. Insights into the deliberations of the International Liaison Committee on Resuscitation task force members are provided in Values and Preferences sections. Finally, the task force members have prioritized and listed the top 3 knowledge gaps for each population, intervention, comparator, and outcome question.